(untitled) (Global Conference on Multidisciplinary Research and Innovation, 2026)
This article explores the aesthetic dimensions of sport, positioning it not merely as a test of physical prowess but as a domain of profound artistic and philosophical expression. By analyzing the concept of "the beautiful movement," the paper examines how sport harmonizes the biological constraints of the human body with the fluidity of performance. Drawing on classical aesthetic theories and contemporary philosophy, it argues that sport acts as a performative art where the athlete transforms physical effort into kinetic beauty. The study concludes that the appreciation of sport transcends competitive outcome, rooted instead in the embodiment of human potential and grace.